Assessment Of Water Quality And Bottom Supplies In The Bottom Of The Mekong River (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article presents the results of studies of the content of heavy metals in bottom sediments in the lower reaches of the Mekong River (3 estuaries in Ben Tre). The results of the content of heavy metals for 20 research sites were analyzed and compared with the national standards of Vietnam, which are used to assess the level of adverse effects on aquatic animals and river ecosystems, as well as with similar standards adopted in various countries of the world. When compared with the standards, the content of heavy metals in the study area (Ben Tre province) was quite high. The tributaries flowing into the main river also have a relatively high content of heavy metals, which proves that, in addition to pollution from the upper reaches of the river, socio-economic activities in the catchment, including land reclamation, also have a strong effect on the accumulation of heavy metals in channel sediments. In addition, the authors, comparing the content of heavy metals, both with the established standards of Vietnam and with the standards of some countries of the world, creating a basis for rational agriculture and sustainable development.